Aurah and custodianship of adopted child guided decisions according to syaria - Muhammad Husni, Ahmad; Muhammad Husni, Amin (Zes Rokman Resources (2131022-P), 2021)
Adoption of children happens because of a marriage from spouses that are not blessed by any offspring even they have gone through series of treatment and numbers of procedures to get child, or it also happens due to the soul that love children so much, as well as to help the orphans or neglected children. This article mainly to give exposure and solution regarding to the aurah and guardianship of the child and his or her adopted family, which is known by public, they do not have any blood relation between one another. This study conducted based on the analysis of the library books, legal references and other sources from the internet and also the Malaysian Children adoption act. The result from this study shows that the Malaysian aurah and custodianship is an issue regarding the general laws that could change according to certain cases and situation that are faced by the involved parties. The actions taken needed to be considered upon the general implication that are about to be issued later.